The Menyoal Tingginya Angka Disepensasi Nikah di Kabupaten Pekalongan - Novi Alviani (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2022)
This study provides an insight into the problem of the high number of marriage dispensations as a result of the renewal of regulations regarding the marriage age limit in Pekalongan Regency. Marriage dispensation is closely related to the phenomenon of early marriage which is rife in various circles of society. Changes in the regulation of marriage restrictions are officially stated in Law no. 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage. Article 7 paragraph (1) which originally stated that the age limit for marriage for men was 19 years and for women was 16 years, is now equated with 19 years for men and women. In fact, on the contrary, although the government has updated the regulation on limiting the age of marriage, it has not reduced the number of early marriages, but the demands for dispensation for marriage are higher, not least in Pekalongan Regency, which ranks at the top. The 3 most cases of early marriage in Java. Middle. This study aims to determine the factors causing the high rate of marriage dispensation in Pekalongan Regency. The research method used is library research with a normative legal approach based on the latest developments or legal norms. The results of this study indicate that cases of marriage dispensation applications at the Kajen Religious Court continue to increase every year. Several factors that cause the high number of marriage dispensations internally are due to the tradition of the Gunung people to marry off children quickly. In addition, due to the renewal of regulations regarding the prohibition of marriage, the rise of early marriage, the number of cases of pregnancy outside of marriage, and due to the pandemic.